2012
DOI: 10.1007/s00415-012-6664-6
|View full text |Cite
|
Sign up to set email alerts
|

Role of magnetic resonance imaging, cerebrospinal fluid, and electroencephalogram in diagnosis of sporadic Creutzfeldt-Jakob disease

Abstract: Sporadic Creutzfeldt-Jakob disease (sCJD) is a rapidly progressive dementia (RPD) that can be difficult to identify ante-mortem, with definitive diagnosis requiring tissue confirmation. We describe the clinical, magnetic resonance imaging (MRI), cerebrospinal fluid (CSF), and electroencephalogram (EEG) measures of a small cohort of 30 patients evaluated for RPD. Clinical and diagnostic measures were cross-sectionally obtained from 17 sCJD patients (15 definite, 2 probable), 13 non-prion rapidly progressive dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
31
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 38 publications
4
31
0
Order By: Relevance
“…These elements could explain the low sensitivity reported in some studies: 44% [171]; 50% [97], 58.4% [37]; 64% [149]; 65% [125]; 66% [172]. One study even concluded as to the lack of usefulness of EEG in discriminating sporadic CJD from other non-prion rapidly progressive dementia (sensitivity 41%; specificity 54%), but the results of this study is limited by the low number of patients included (n = 30) [167].…”
Section: Rapidly Progressive Cognitive Disorders: Prion Diseases (Tramentioning
confidence: 81%
“…These elements could explain the low sensitivity reported in some studies: 44% [171]; 50% [97], 58.4% [37]; 64% [149]; 65% [125]; 66% [172]. One study even concluded as to the lack of usefulness of EEG in discriminating sporadic CJD from other non-prion rapidly progressive dementia (sensitivity 41%; specificity 54%), but the results of this study is limited by the low number of patients included (n = 30) [167].…”
Section: Rapidly Progressive Cognitive Disorders: Prion Diseases (Tramentioning
confidence: 81%
“…Current diagnosis of CJD relies on a combination of results from magnetic resonance imaging, cerebrospinal fluid analysis, and electroencephalography (Zerr 2009;Wang et al 2013). In addition, new technologies, such as quakinginduced conversion analysis for detecting an ultra-trace amount of PrP Sc in the cerebrospinal fluid (Atarashi et al 2011;McGuire et al 2012;Sano et al 2013;Cramm et al 2015;Orrú et al 2015), nasal brushings (Orrú et al 2014), urine (Moda et al 2014), or blood (Orrú and Caughey 2011;Orrú et al 2012), have presented new opportunities for early diagnosis.…”
Section: Preclinical Diagnosismentioning
confidence: 99%
“…Some studies hypothesized that the spongiform changes in CJD could restrict water molecule diffusion and lead to decreased MD and a relative preservation of FA. [50,51] Along with the changing of DWI hyperintensity in the disease course of CJD, MD decreases in the early stage of disease and tends to be normal or increase in the terminal stage. The increasing MD is associated with more significant loss of function.…”
Section: Diffusion Tensor Imagingmentioning
confidence: 99%